DATA-DRIVEN STORYTELLING IN PERFORMING ARTS: INNOVATION AT THE INTERSECTION OF CREATIVITY AND ANALYTICS - Sripada, Pushpa Nagini; N, Nivetha; S, Suganya; Arumugam, Suresh; Thiruchenduran, Mohana; Bist, Ankur Singh (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Data analytics, digital technology and interactive media has transformed the creative industries including the performing arts significantly due to its quick spread. Traditionally, storytelling has been very reliant on intuition of art as well as cultural narratives and interpretation by the audience especially in the theatre, dance and live performance field. However, the arrival of data-driven approaches has unveiled new opportunities of narrative design augmentation and the ability to interact with the audience and be flexible in performance. The article addresses the concept of data-driven storytelling in performing arts and how analytic knowledge and creative activities can be used together to increase the intensity of immersive and receptive performance experiences. The study also offers a comprehensive framework, combination of data collection, analytical processing, creative assimilation and performance execution to support new storytellings methods. Analysis is done on the data of the audience behavior, feedback system, interactive technology to identify the effects on the development of a story, or a stage performance. A descriptive comparison between the traditional storytelling systems and the data-driven storytelling systems underline a significant improvement in the viewer engagement, interactivity and personalization, and creative versatility in case analytical knowledge is incorporated into the creative process. The findings show that the utilization of data analytics in performing arts would help to support the needs of the directors, performers, production teams and provide the audience with more customised and dynamic experiences. As much as the benefits can be achieved, there are other concerns that are paramount when effecting the changes and these are, technological infrastructure requirements, ethical concerns that are raised about privacy of information as well as the fact that artistic originality has to be maintained. The research ends with the opinion that the future of the performing arts ecosystem will require interdisciplinary collaboration between artists, data scientists and technologists in order to devise sustainable and innovative paradigms of storytelling.